Options for Strengthening East African Community's Trade Integration - World Bank (Washington, DC, 2012)
The treaty for the establishment of the East African Community (EAC) was signed in November 1999 by Kenya, Tanzania, and Uganda. The treaty, which entered into force in June 2000, aims a comprehensive integration process comprising of trade, economic, and political integration. The ultimate objective is to establish a political federation in 2015 through a progression of trading and economic arrangements (customs union, common market, and monetary union) as well as host of joint projects to develop regional infrastructure, manage regional commons, and produce regional public goods. Given the small size and the low income level of the member countries, aiming for a comprehensive integration is the right strategy, which will enable them to pull their resources together, broaden their markets, harmonize their policies, and enhance their competitiveness collectively to be able to expand their productive capacity and regional and global trade to accelerate growth. Burundi and Rwanda were accepted a new members of the EAC in November 2006. Their membership is expected to be effective in the second half of 2007. This report suggests a list of core priority areas and recommends broad direction of reforms. Its analysis and recommendations will serve as a useful contribution to the ongoing negotiations among the member states for an EAC common market as well as to efforts to harmonize programs between Common Market for Eastern and Southern Africa (COMESA), South African Development Community (SADC), and EAC.